Food Retail Resilience Pre-, during, and Post-COVID-19: A Bibliometric Analysis and Research Agenda - Rebeka-Anna Pop; Dan-Cristian Dabija; Cristina Bianca Pocol (Foods, 2024)
This paper aims to conduct a bibliometric mapping and systematic review of the food retail industry’s resilience strategy in the context of COVID-19. Specifically, we aim to identify relevant research gaps in the industry during the pre-, during, and post-pandemic periods and highlight the differences between B2B and B2C sectors. We analyzed articles in the Scopus database from 2019 to 2022 using the PRISMA method for article selection, resulting in a total of 69 articles. We employed a VOS viewer for bibliometric mapping. Our analysis revealed that most studies focused on the impact of COVID-19, with only a few examining the pre- and post-pandemic periods critically. In the B2C context, we identified two major topics: changes in purchasing and consumption behavior, and food waste and safety. In the B2B sector, the two most recurrent subjects were retailers’ strategies and supply chain management. This study provides valuable insights for policymakers by exploring industry trends and for scholars by highlighting future research agendas based on the identified topics.